Uzbekistan National Wrestling: The Basis of Physical Education and Spiritual Performance - Rakhimov Bekzod Chorievich (Scientific Trends, 2024)
This article highlights the role and importance of Uzbek national wrestling in physical education and spiritual development. The role of wrestling in educating the younger generation in the spirit of a healthy lifestyle, courage, fortitude and patriotism is analyzed. The international prestige of our national sports heritage and its importance in strengthening our national pride are also discussed.
Keywords: Uzbek national wrestling, physical education, spiritual development, national sports, education of the younger generation, healthy lifestyle, patriotism, national heritage, international prestige.